Rancang Bangun Aplikasi Manajemen Lembaga Pendidikan Al-Qur’an Metode Tartila Berbasis Mobile dengan Model Waterfall - Rokhiyatus Sa'diyah; Muhammad Imron Rosadi (Sekawan Institut, 2025)
The management of Al-Qur'an educational institutions, particularly Al-Qur'an Education Parks (TPQ), still faces various obstacles in the administrative process, such as the lack of integration in recording student data, inefficient management of study schedules, and difficulties in monitoring teacher performance on a regular basis. These problems cause the administrative process to be slow and inaccurate. This study aims to design and develop a mobile-based management application for Al-Qur'an educational institutions that implement the Tartila Method in Sukorejo Dis-trict, using the Waterfall development model. Data collection was carried out through observa-tion, interviews, and literature studies to obtain comprehensive user requirements. The system was developed using Flutter as the user interface, Dart as the programming language, Laravel for the backend, and MySQL as the database. The system design utilized UML, ERD, and interface prototypes through Figma. Testing was conducted using Blackbox Testing and the System Usability Scale (SUS). The test results showed that all system features functioned properly according to user needs. The SUS score of 71.6 falls into the Good (acceptable) category, indicating that the application is easy to use and accepted by users. Thus, the developed system is considered effective in improving administrative efficiency, facilitating the monitoring of santri development, and supporting digital transformation in Tartila Method-based Al-Qur'an educational institu-tions..